Surrogacy around the world - Lasker, shamima Parvin (Bangladesh Journal of Bioethics, 2017)
Surrogacy is an encouraging management for many childless couples and can hypothetically resolve many unbearable pain that they are confronted. Initially surrogacy treatment was frowned upon, however, surrogacy is more popularly accepted now a day. Though, surrogacy has not yet recognized by 199 country in the globe. Different country has different regulations on surrogacy. However, “there are some indication of the degree of divergence between oﬃcial discourse and actual practice of surrogacy throughout world”. There are positive changes in attitude toward surrogacy has been seen in some countries. This special issue of Bangladesh Journal of Bioethics has been organized on surrogacy to see the current thinking of surrogacy around the world and how people come out from the social, religious and political framework.